The goverment savings plan new for occupational health mangement. Where is the working women’s health reform with mutuas of 2014? - Romero Coronado, Mª Ángeles (Nómadas. Critical Journal of Social and Juridical Science, 2015)
Labor market it´s a changing and accelerated world which reflects the basic social needs. Since the incorporation of women into de labor market in the industrial revolution up to the present time, it´s been reclaiming a fully incorporation of all the labor aspects, among including the occupational health for both men and women. The necessity adaption to gender of the occupational health has come to be objective of public policy, but has not been translated into a real application. The ongoing economic crisis has led a new reform of the management MUTUAS of occupational accidents and diseases, vital institutions in the national system. This reform gives more freedom to the MUTUAS and makes it more difficult to apply a gender perspective to the recognition of temporary disabilities and diseases of women.